Contemporary American Indian Literatures and the Oral Tradition - Brill de Ramírez, Susan Berry, 1955- (Book collections on Project MUSE., 1999)
A literary study of Native American literature analyzes its sources in oral tradition, offering a theory of "conversive" critical theory as a way of understanding Indian literature's themes and concerns.